2007
DOI: 10.3989/cyv.2007.v46.i2.249
|View full text |Cite
|
Sign up to set email alerts
|

Vidrios y Vitrocerámicos Bioactivos

Abstract: Since the late 1960´s, a great interest in the use of bioceramic materials for biomedical applications has been developed. In a previous paper, the authors reviewed crystalline bioceramic materials "sensus stricto", it is to say, those ceramic materials, constituted for non-metallic inorganic compounds, crystallines and consolidates by thermal treatment of powders at high temperature. In the present review, the authors deal with those called bioactive glasses and glassceramics. Although all of them are also ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(23 citation statements)
references
References 36 publications
2
16
0
5
Order By: Relevance
“…9,12,13,17,19,20 Convém ainda citar alguns metais e ligas, desde que sob condições especiais de tratamento superficial. 11,21 Por suas características intrínsecas e natureza distinta, é de se esperar que os materiais bioativos apresentem índices de bioatividade variados, ou seja, diferentes tempos para o estabelecimento de ligação com o tecido.…”
Section: Vidros E Vitrocerâmicas Bioativasunclassified
See 1 more Smart Citation
“…9,12,13,17,19,20 Convém ainda citar alguns metais e ligas, desde que sob condições especiais de tratamento superficial. 11,21 Por suas características intrínsecas e natureza distinta, é de se esperar que os materiais bioativos apresentem índices de bioatividade variados, ou seja, diferentes tempos para o estabelecimento de ligação com o tecido.…”
Section: Vidros E Vitrocerâmicas Bioativasunclassified
“…Dessa forma, de modo geral existem vidros bioativos com elevado índice de bioatividade e baixas propriedades mecânicas, e cerâmicas e vitrocerâmicas com elevadas propriedades mecânicas e baixo índice de bioatividade. 9,20,22 Em se tratando apenas dos vidros e vitrocerâmicas bioativas, tem sido observado na literatura que somente uma série de composições limitada exibe alto índice de bioatividade. A relação entre composição e bioatividade para vidros do sistema SiO 2 −CaO−Na 2 O−P 2 O 5 , obtidos pelo processo de fusão/solidificação, é mostrada na Figura 1, na qual é assumida concentração constante de 6% em massa de P 2 O 5 .…”
Section: Vidros E Vitrocerâmicas Bioativasunclassified
“…Many investigations have been carried out regarding the stability of 12CaO·7Al2O3 phase in the Al2O3-CaO system. [15][16][17] Among them, Nurse et al concluded that the 12CaO·7Al2O3 phase was not stable under strictly anhydrous conditions, however was stabilized by the presence of moisture.…”
Section: Characterizationmentioning
confidence: 99%
“…BioveritÒ II, a mica-containing glass ceramic from which ossicular replacement prostheses and other implants are routinely fabricated. 31,32 We use a sulfonic acid modification to increase the amount of loaded ciprofloxacin in a mesoporous silica layer and show its biocompatibility and its effectiveness in combating bacteria in vitro. Additional coatings generated from silanes are added to attenuate the typical initial burst release behavior of drug delivery systems and retard the delivery of the drug.…”
Section: 30mentioning
confidence: 99%